(untitled) (MCIT: Proceedings of International scientific and practical conference, 2019)
On the base of exergy-based approach it is shown that for the ventilation systems there are operating modes for which heat recovery increases exergy of fuel expended to provide the ventilation air compared to cases without bringing any recovery of heat and additional power consumption to drive the air flow by the fans. For the specified system, in case of switching ventilation unit to the operation mode of lower values of spent fuel exergy it is possible to provide annual saving from 5 to 15 % of the primary energy sources.